Clinical ethics: Consent for vaccination in children - Wilkinson, D; McBride, A (BMJ Publishing Group, 2021)
The prospect of vaccinating children and young people against COVID-19 raises questions that apply more widely to vaccination in children. When can children or adolescents consent, on their own, for vaccination? What should happen if children and their parents disagree about the desirability of a vaccine? When, if ever, should vaccination proceed despite a child’s dissent or apparent refusal? A range of ethical dilemmas may arise (box 1). In this article, we will address general ethical issues relating to consent for vaccination, highlighting their relevance to COVID-19. We will not address the wider ethical questions of whether or when children should be vaccinated against COVID-19.